The benefits of preserving residual hearing following cochlear implantation: a systematic review. (2nd August 2021) - Schaefer, Simone; Sahwan, Maryam; Metryka, Aleksandra; Kluk, Karolina; Bruce, Iain A.
Abstract: Objective: Systematically review the current literature for evidence on the "real-life" benefits of hearing preservation cochlear implantation (HPCI) for children and adults. Design: Systematic search of Pubmed, MEDLINE, EMBASE, CINHAL and Cochrane Library for MesH terms hearing ¸ preservation and cochlear implantation . Inclusion criteria were the "real-life" benefit of HPCI i.e. other than pre- and post-operative pure tone thresholds. Exclusion criteria were non-English language, conference abstracts, reviews and animal and cadaveric studies. Risk of bias was assessed using the Evidence Project Tool. Study sample: 37 studies that matched criteria for review with 8/37 including children and 29/37 including adults. Results: HPCI was associated with better speech perception in noise in 18/26 papers and better music perception in 4/5 papers. There was no significant benefit reported in speech perception in quiet (14/20 papers) or binaural cues (3/4 papers), nor was there convincing evidence of HPCI outperforming bimodal users (5/7 papers). QoL scores were high amongst HPCI patients (2/2 papers). Interpretation of findings was hindered by small study groups and significant heterogeneity in various parameters. Conclusion: Current literature on the "real-life" benefit of HPCI, although limited, supports the existence of meaningful benefit, especially in speech perception in noise and music perception .